Output Hysteresis and Optimal Monetary Policy - Vaishali Garga; Sanjay R. Singh (University of California, Department of Economics, 2019)
We analyze the implications for monetary policy when deficient aggregate demand can cause a permanent loss in potential output, a phenomenon termed as output hysteresis. In the model, incomplete stabilization of a temporary shortfall in demand reduces the return to innovation, thus reducing TFP growth and generating a permanent loss in output. Using a purely quadratic approximation to welfare under endogenous growth, we derive normative implications for monetary policy. Away from the zero lower bound (ZLB), optimal commitment policy sets interest rates to eliminate output hysteresis. A strict inflation targeting rule implements the optimal policy. However, when the nominal interest rate is constrained at the ZLB, strict inflation targeting is sub-optimal and admits output hysteresis. A new policy rule that targets output hysteresis returns the output to the pre-shock trend and approximates the welfare gains under optimal com- mitment policy. A central bank unable to commit to future policy actions suffers from hysteresis bias: it does not offset past losses in potential output.
Keywords: E52; E32; O42; 330; zero lower bound; optimal monetary policy; endogenous potential output; hysteresis bias